THE AUTOMOBILE TIRES VULCANIZATION METHOD REPAIR PROCESS EXPERIMENTAL INVESTIGATION - Orysenko, O. V.; Kryvorot, A. I.; Ilchenko, V. V.; Filipova H. А. (Academic journal Industrial Machine Building Civil Engineering, 2018)
In the article local repair automobile tires expediency by vulcanization means in mechanical damage carcass case is shown. It has been established that analytical and experimental data on determining the required temperature of the heating element have a significant discrepancy. It was found that on the vulcanization degree among all factors temperature and pressure on the welding surfaces are the most influential. After processing the experimental data and using the static methods, mathematical dependence of the temperature on the welding surface from the heating element temperature and on the welding surfaces as a second-degree polynomial is obtained. In order to verify the research results reliability, the control welding of the automobile tires with cord lateral rupture was conducted, which gave positive results.